Burning down the Haus : punk rock, revolution, and the fall of the Berlin Wall - Mohr, Tim (Algonquin Books of Chapel Hill, 2018)
"The history of how teenage East German punk rockers played an indispensable role in bringing down the Berlin Wall"--